Interpretation of Discordant Rifampicin Susceptibility Test Results Obtained Using GeneXpert vs Phenotypic Drug Susceptibility Testing. (5th July 2020) - Huo, Fengmin; Ma, Yifeng; Liu, Rongmei; Ma, Liping; Li, Shanshan; Jiang, Guanglu; Wang, Fen; Shang, Yuanyuan; Dong, Lingling; Pang, Yu
Abstract: Background: The 3-month difference in turnaround time between Xpert and conventional phenotypic drug susceptibility testing (pDST) causes patient treatment challenges when pDST rifampin (RIF) susceptibility results and earlier Xpert results disagree, resulting in unnecessary tuberculosis (TB) patient exposure to toxic second-line drugs. Here, the prevalence of discordant RIF susceptibility test results, specifically Xpert (resistant) vs pDST (susceptible) results, was determined. Methods: Tuberculosis patients enrolled between January 2015 and June 2018 at Beijing Chest Hospital who consecutively tested positive for RIF resistance using Xpert then negative using pDST were studied. DNA sequences and minimal inhibitory concentration (MIC) results provided insights for understanding discordant results. Results: Of 26  826 patients with suggestive TB symptoms undergoing Xpert MTB/RIF testing, 728 diagnosed as RIF-resistant were evaluated. Of these, 118 (16.2%) exhibiting Xpert RIF resistance and phenotypic RIF susceptibility yielded 104 successfully subcultured isolates; of these, 86 (82.7%) harbored rpoB gene RIF resistance–determining region mutations and 18 (17.3%) did not. The Leu511Pro (25.0%) and Leu533Pro (17.3%) mutations were most frequently associated with discordant RIF susceptibility test results. Of the 86 isolates with rpoB mutations, 42 (48.8%) with MICs ≤1.0 mg/L were assigned to the RIF-susceptible group, with Leu511Pro being the most common mutation observed. Isolates with a very low bacterial load were most frequently misdiagnosed as RIF-resistant by Xpert. Conclusions: Approximately one-sixth of RIF-resistant TB isolates identified via Xpert yielded discordant pDST results due to questionable interpretation of specific "disputed" mutations. Thus, a diagnostic flowchart should be used to correctly interpret Xpert RIF resistance results to best guide patient treatment.